(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Background: Diabetic retinopathy (DR) is a leading cause of blindness in developed countries. Factors like inadequate glycemic control, hypertonia, blood lipid disorder, and renal disease, are known to negatively affect vision, and may cause loss of sight. Some studies demonstrate that there are additional contributors to the development of DR. Purpose: To investigate the relationship between serum resistin levels and diabetic retinopathy in obese patients with type 2 diabetes mellitus (T2DM). Materials and Methods: Seventy-nine patients (mean age, 59.57 ± 4.01 years; mean duration of diabetes, 9.97±2.46 years; mean HbA1c, 10.31±1.89%) with T2DM and body mass index (BMI) > 24.99 kg/m2 underwent examination. Serum resistin levels were measured by ELISA. Analysis of variance was used for data analysis. Results: The serum resistin levels were 4.84 ± 0.41 ng/mL (95% CI, 4.26 to 5.41) in the non-diabetic control group and gradually increased with the severity of DR to the maximum of 6.19 ± 0.65 ng/mL (95% CI, 5.27 to 7.11) in moderate to severe non-proliferative DR (P = 0.18). Conclusion: Patients with proliferative DR and any risk factors had moderately increased mean serum resistin levels, with the highest values being noted in duration of diabetes of more than 10 years.